Information seeking behavior among undergraduate students in Universiti Tun Hussein Onn Malaysia / Muhamad Saufi Che Rusuli, Raja Abdullah Raja Yaacob, Rosmaini Tasmin and Norazlin Hashim - Tasmin, Rosmaini (Faculty of Information Management, 2013)
This study attempts to determine the information seeking behaviour and use of information needs by undergraduate students at Universiti Tun Hussein Onn Malaysia (UTHM) Johor. The overall purpose of the study was to identify the problems that undergraduate students encounter, identify their information needs and determine their awareness of library services available to them. The study collected empirical data on the information requirements of graduate students. Data were randomly selected from 357 undergraduate students across six faculties and 200 filled in questionnaires were returned, giving an overall response rate of 56 per cent. Findings indicate that guidance in the use of library resources and services is necessary to help students meet some of their information requirements. The study found that library books, lecturer notes, lecturer handouts and textbooks are the most popular sources of information. The Online Public Access Catalogue (OPAC) were the most frequently used IT based sources and facilities. Email was the most popular among the Interned based services and applications. On the whole, respondents perceived UTHM library collections, services and facilities as adequate to meet their information seeking behavior and information needs effectively.